Lack of lecturer clarity during instruction: Possible reason for poor throughput? - Segabutla, M.H.; Evans, R. (South African Journal of Higher Education, 2019)
In South Africa, students’ academic success in tertiary environments is generally low, despite governmental or institutional interventions. This article, underpinned by the General Model of Instructional Communication by McCroskey, Valencic and Richmond (2004), explores participant lecturers’ perceptions of lecturer clarity during instruction, and their students’. A mixed methods case study was conducted, with a convenience sample of seven lecturers, interviewed and observed in situ. Questionnaires were completed by 252 first year students at a South African university of technology. Content and statistical analysis of the data revealed that a mismatch existed between lecturers’ perceptions of their own instructional clarity and their students’. The high percentage of students who felt lost during a lecture suggests a high level of instructional dissonance (Evans, 2005) which might account for a less-than desirable academic throughput. We recommend that institutions quality assure lecturers’ oral, written, content and process clarity prior to and during appointment.